Protonation-induced changes in the photophysical properties of a phthalocyanine and a covalently-linked, phthalocyanine-C60 fullerene dyad - Bottari, Giovanni; Kahnt, Axel; Guldi, Dirk Michael; Torres, Tomas (ECS Journal of Solid State Science and Technology, 2013)
The effect of the protonation on the photophysical properties (i.e., ground state and excited state properties) of Zn(II)phthalocyanine (Zn(II)Pc) 2 and covalently-linked, electron donor-acceptor Zn(II)Pc-C 1 have been investigated. On one hand, important changes in the absorption features of these two systems have been seen upon addition of trifluoroacetic acid due to protonation of some meso nitrogens of the Pc moiety. On the other hand, significant changes in the lifetime of the singlet excited states - in the case of 1 and 2 - and of the charge-separated state - in the case of 1 - were also observed. We reckon that this study, unprecedented in term of the study of the time-resolved excited state features of a protonated Pc-C conjugate, will contribute in terms of shedding light toward a better understanding of photoinduced processes in Pc-based systems. © 2013 The Electrochemical Society.